Ideology, social theory, and the environment - Sunderlin, William D. (Rowman and Littlefield Publishers, 2003)
Does human population growth threaten the environment, or does it guarantee we will safeguard it? Is economic growth the key ecological problem, or is it in fact the solution? What will be the leading force to save the planet: civil society, government, or private enterprise? This book shows that these polemical debates are governed not so much by access to "facts" as they are by the political ideology of the expert advancing a particular argument. Moreover, the thoughts of these experts tend to be based largely in just one of three competing streams of political thought: the left, the center, or the right. Drawing on social theory, the author explains the philosophical origins of this tendency to rely on just one of three traditions, and why this poses a serious obstacle to conceptualizing the cause, nature, and resolution of environmental problems. Sunderlin argues that laying the foundation for a livable world involves giving conscious and dedicated attention to the core tenets of all three political traditions: action against class inequality and advocacy of social justice within and among countries; reformation of laws and policies emanating from the halls of power and technological innovation in centers of research; and wholesale cultural change and promotion of individual initiative, responsibility, and creativity.